MATERNAL BEHAVIOR RELATIONS, ATTITUDES AND KNOWLEDGE AND INFORMATION EXPROSURE TO PNEUMONIA EVENTS IN CHILDREN - Jumiati; Qonita (Journal Of Applied Health Research And Development, 2020)
Background: Pneumonia is the leading cause of under-five mortality in the world. This disease accounts for 16% of all deaths of children under 5 years, which causes death to 920,136 children under five, or more than 2,500 per day, or an estimated 2 children under five die every minute in 2015. The number of pneumonia cases in children under five in Indonesia in 2015 In 2017, there were 447,431 cases (46.34%), while in Banten Province itself there were 30,402 cases (62.35%) and the number of under-five deaths due to pneumonia in Banten was 31 cases. Pneumonia cases in children under five in Cilegon City in 2017 saw a significant decrease from 797 toddlers (2016) to 660 toddlers (2017) consisting of 381 boys and 279 girls. This study aims to see the relationship between the incidence of pneumonia in children under five in Cilegon City which is caused by the mother's behavior, attitudes, knowledge and information exposure. The population and sample in this study were 366 mothers who had famous toddlers in 8 Puskesmas in Cilegon City. The method used is quantitative methods with cross sectional design. Data collection was carried out by survey, namely the researcher conducted direct interviews with respondents using a questionnaire. The research results obtained the following data; There were 97 toddlers who had pneumonia or 26.5%, almost all of them 94.5% of mothers had good knowledge about pneumonia, 46.7% of mothers had sufficient behavior and 49.5% of mothers had sufficient attitudes and more than half of them 70.2% of mothers had not been exposed to information about pneumonia. The Bivariate results found that attitude and information exposure had a significant relationship with the incidence of pneumonia, while behavior and knowledge had no significant relationship with the incidence of pneumonia among toddlers in the city of Cilegon. From the results of this study, it is hoped that the Cilegon City Health Office can increase socialization and counseling about pneumonia through cooperation with related agencies so that it can improve the degree of public health.